Sequential Keraring implantation and corneal cross-linking for the treatment of keratoconus in children with vernal keratoconjunctivitis - Abozaid MA (Clinical Ophthalmology, 2017)
Mortada A Abozaid Ophthalmology Department, Faculty of Medicine, Sohag University, Sohag, Egypt Purpose: The purpose of this study was to assess the safety and efficacy of femtosecond laser-assisted Keraring implantation followed by transepithelial accelerated corneal collagen cross-linking (CXL) for the treatment of keratoconus in children with vernal keratoconjunctivitis (VKC).Study design: This is a prospective interventional non-comparative case series.Patients and methods: Eighteen eyes of 11 children with keratoconus and VKC were included in this study. All the cases were treated with femtosecond laser-assisted Keraring implantation followed after 2 weeks by transepithelial accelerated CXL, and the patients were followed up for 1 year.Results: The preoperative mean uncorrected visual acuity (UCVA) was 1.01±0.2 (logMAR), whereas the postoperative mean UCVA was 0.6±0.2. The preoperative mean best-corrected visual acuity (BCVA) was 0.6±0.1, whereas the postoperative mean BCVA was 0.40±0.2. The preoperative average keratometry was 50.3±2.7 D, whereas the postoperative average keratometry was 45.8±3.1 D. Conclusion: The results of this study suggest that femtosecond laser-assisted Keraring implantation followed by CXL is safe and effective in the management of keratoconus in children with VKC. However, studies with a longer follow-up period are needed. Keywords: cross-linking plus, intrastromal corneal ring segments, pediatric keratoconus, spring catarrh